Platelet count and Superoxide Dismutase as a marker for severity of Plasmodium infection. - Shetty, Archana; Srinivas, Teerthanath; Srinivas, Hariprasad (International Journal of Research in Medical Sciences, 2017)
Background: Malaria continues to be an important public health problem in developing and underdeveloped countries with high morbidity and mortality. It continues to be one of the major public health problems in India. Plasmodium vivax is the major parasite type causing malaria and Plasmodium falciparum is the major cause of serious and complicated disease. Haematological abnormality which is most commonly seen in malaria is thrombocytopenia followed by anaemia. Identification of predictors of disease severity is critical to improve patient care. This study was undertaken to evaluate the severity of thrombocytopenia and erythrocyte SOD level in infections by plasmodium vivax, falciparum and mixed infection. Methods: A hospital based cross sectional study done on confirmed cases of malaria in a tertiary care hospital in costal Karnataka. All patients tested positive for malaria (either by rapid diagnostic test or peripheral smear) were included and patients presenting with fever who were but treated empirically for malaria were excluded in the study. The type of malarial infection was diagnosed with QBC and thin peripheral smear method; platelet count was done by automated cell counter and estimation of superoxide dismutase (SOD) by nitro blue tetrazolium chloride reduction method. Results: A total of forty infected malaria patients were evaluated. The age range of the infective patients were between 15 to 70 years. Males were more commonly affected than females in the ratio of 5.6:1. The most common type of malaria infection was from P. vivax and mixed infection (40% each) followed by P. falciparum (20%). Majority (50%) of the patient had severe infection followed by mild infection (35%) and moderate infection. The mean platelet count was 1,14,250/cu mm in P.falciparum, 85,000/cu mm in P.vivax infection and 60,625/cu mm in mixed infection. The mean platelet count was least (56,181/cu mm) in severe infective patients than in moderate (91,666/cu mm) and mild (1,21,500/cu mm) infections. The SOD levels was reduced more in P. vivax (26.43U/mg Hb) and mixed infection (20.96U/mg Hb) than P.falciparum (32.74U/mg Hb). SOD levels were proportionally low in severe infection (14.94U/mg Hb), when compared to moderate (20.35 U/mg Hb) and mild infection (32.19 U/mg Hb). Conclusions: Anaemia and thrombocytopenia are the most frequent haematological complications associated malaria. Thrombocytopenia is associated with increase in parasite density and severity of the infection, its more common in P.vivax and mixed infection than P.falciparum infection. The SOD level substantially reduces depending on the severity of malaria. Thrombocytopenia and reduced SOD level is a powerful predictor of disease severity. These parameters could be useful in the clinical approach of patients with malaria for prompt timely initiation of anti-malarial therapy and reduce the mortality.